2017
DOI: 10.29133/yyutbd.305106
|View full text |Cite
|
Sign up to set email alerts
|

İnebolu Havzası Topraklarının Erozyon Duyarlılık Durumları ve Arazi Kullanımı/Arazi Örtüsü ile Olan İlişkisinin Belirlenmesi

Abstract: Özet: Toprak ve su kaynaklarımızı tehdit eden doğal ve yapay birçok unsur bulunmaktadır. Özellikle yanlış arazi yönetimi ve kullanımlarından kaynaklanan bu tehditlerin en önemlilerinden bir tanesi de toprak erozyonudur. Erozyon risk durumlarının belirlenmesine yönelik toprak duyarlılık indekslerinin kullanılması, özelikle erozyon araştırmalarında önemli yer teşkil etmektedirler. Toprağın erozyona duyarlılığı, yağış veya yüzey akışla toprağın parçalanmaya direncidir. Bu çalışmanın amacı, İnebolu Havzası toprakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…On the other hand, the erosion rates of the soil samples were found to have significantly positive correlations with the dispersion rate (0.622**) and K factor (0.653**) values, which are the parameters used in assessing structural stability, at 1% level, and significantly negative correlation with aggregate stability (-0.546**) at 1% level (Table 2). Different researchers have obtained similar findings in their studies in different regions (García-Orenes et.al., 2009;Özdemir et al, 2015;Saygın et al, 2017). Gülser (2004) found that cropping treatments improved infiltration ratio by increasing sructural stability and porosity that can lead to the benefits of reduced erosion and improved soil water storage.…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the erosion rates of the soil samples were found to have significantly positive correlations with the dispersion rate (0.622**) and K factor (0.653**) values, which are the parameters used in assessing structural stability, at 1% level, and significantly negative correlation with aggregate stability (-0.546**) at 1% level (Table 2). Different researchers have obtained similar findings in their studies in different regions (García-Orenes et.al., 2009;Özdemir et al, 2015;Saygın et al, 2017). Gülser (2004) found that cropping treatments improved infiltration ratio by increasing sructural stability and porosity that can lead to the benefits of reduced erosion and improved soil water storage.…”
Section: Results Discussionmentioning
confidence: 99%
“…He found that the organic matter, bulk density, aggregate stability and erosion sensitivity of the soil had statistically significant changes due to the transformation of the forest and pasture areas into agricultural use. Eraslan et al (2017) examined the relationship between the erosion sensitivities of the soil in the İnebolu Basin, the way the land was used and the vegetation cover on the land. They emphasized that there were statistically significant relationships between the sensitivity to erosion and clay content; and between vegetation cover and coverage.…”
Section: Introductionmentioning
confidence: 99%